2019
DOI: 10.1039/c9ra01539f
|View full text |Cite
|
Sign up to set email alerts
|

Black titania nanotubes/spongy graphene nanocomposites for high-performance supercapacitors

Abstract: A simple method is demonstrated to prepare functionalized spongy graphene/hydrogenated titanium dioxide (FG-HTiO2) nanocomposites as interconnected, porous 3-dimensional (3D) network crinkly sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The superiority in the water retention capacity of SGO-modified sample can be attributed to the great thermal stability. El-Gendy et al 73 reported that the first humidification step of SGO appeared at the range of 145 C to 173 C. Such degradation in this temperature range is higher compared with SiO 2 (occurring at around 80 C 74 ) and TiO 2 (occurring between 25 C and 80 C 75 ) and provides a better support in the water retention capacity of CS/SPVA15 composite membrane. The high water retention in inorganic fillermodified sample implies better support of ionic conduction at high temperature (operating temperature of PEMFC at F I G U R E 6 TGA curve of CS/SPVA15 composite membrane with various inorganic fillers >80 C), in which the absorbed water promotes the formation of ionic conducting channels via Grotthuss-type mechanism.…”
Section: Characterisation Of Inorganic Filler-modified Composite Memb...mentioning
confidence: 98%
“…The superiority in the water retention capacity of SGO-modified sample can be attributed to the great thermal stability. El-Gendy et al 73 reported that the first humidification step of SGO appeared at the range of 145 C to 173 C. Such degradation in this temperature range is higher compared with SiO 2 (occurring at around 80 C 74 ) and TiO 2 (occurring between 25 C and 80 C 75 ) and provides a better support in the water retention capacity of CS/SPVA15 composite membrane. The high water retention in inorganic fillermodified sample implies better support of ionic conduction at high temperature (operating temperature of PEMFC at F I G U R E 6 TGA curve of CS/SPVA15 composite membrane with various inorganic fillers >80 C), in which the absorbed water promotes the formation of ionic conducting channels via Grotthuss-type mechanism.…”
Section: Characterisation Of Inorganic Filler-modified Composite Memb...mentioning
confidence: 98%
“…e subject will use 47 infrared reflections attached to the corresponding positions on the body surface to determine the head and torso. Before the formal exercise test, the upper and lower limbs are doubled and statistical data are collected as required [14]. In this study, Weikang cameras were used for sampling.…”
Section: Experiments Of Tai Chi On Knee Jointmentioning
confidence: 99%
“…In this regard, various compositions of rGO and MOs such as manganese oxide (MnO), 19 zinc oxide (ZnO), 20 iron oxide (Fe 2 O 3 ), 21 titanium oxide (TiO 2 ), 22 cobalt oxide (CoO), 23 nickel oxide (NiO), 24 ruthenium oxide (RuO 2 ), 25 and tin oxide (SnO 2 ) 26 or CPs such as polypyrrole (PPY), 27 polyaniline (PANI), 28 and polythiophene (PTh) 29 have been proved as potential electrode materials to improve the capacitance. In our previous works, we have also reported rGO‐CPs 30 and rGO‐ZnO 31 based composites with the highest capacitance of 365.5 F/g.…”
Section: Introductionmentioning
confidence: 99%